Pemberian Hareuta Peunulang di Aceh: Analisis Terhadap Pengurusan Hareuta Peunulang - abdul rauf, zaitun muzana; Hamat, Zahri; Husen Ismail, Faisal (Advances in Humanities and Contemporary Studies, 2020)
Customary practice of giving hareuta peunulang in Aceh Pidie and Aceh Besar issue arising among family members after the death of the (parent). Family members who are dissatisfied with the practice of division will question the status of the property and claim the right to the estate that has been given to one of the children. This study was conducted to identify factors issues arise in the administration of hareuta peunulang in Aceh Pidie and Aceh Besar. This study is a qualitative study with field and library data collection methods. The findings of the study explain that the issue factor stems from three aspects, namely, the property and size of the repeat, the recipient of the next repeat, and the method of giving the repeat. This study proposes for the solution of these three aspects by following the hibah procedures recommended by Islam specifically and according to the muamalat procedures in Islam. This is because the practice of giving peunulang in Aceh is not much different with the grant instrument in Islam except in some particular cases. This study suggests further research related to the administrative management of the estate administration in Aceh to resolve issues that arise in society.